Kesiapan Perusahaan di Indonesia Dalam Menghadapi Revolusi Industri 4.0 - Idham Mahriv; Nisa Alifatuzzahra; Nurbaiti Nurbaiti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main point or The purpose of this study is to find out and understand the preparations that every business company in Indonesia has had to face and will continue to face regarding the current era of industrial revolution 4.0 underway and is currently starting to face further developments in the era that is starting Entering era of industrial revolution 5.0. Industrial Revolution 4.0 or what is also known as